Field control of heliothis zea (boddie) (lepidoptera: noctuidae) using a parasitic nematode - Bong, Joseph Choon Fah (Cambridge University Press, 1986)
Field trials were conducted to assess the effectiveness of a parasitic nematode, the DD136 strain of Neoaplectana carpocapsae Weiser in controlling Heliothis zea (Boddie) on naturally infested sweetcorn.